Peluang Bisnis pada Jasa Kereta Api dan Pesawat Udara - Otok, Bambang Widjanarko; Suhartono, . (Jurnal Widya Manajemen & Akuntansi, 2002)
The aim of this research is to study the application and comparison between models in time series analysis, particularly intervention, variation calendar and transfer function models. Intervention model is used to describe the effect of crisis that happened starting on July 1997 to the fluctuation of the number of train and plane passengers. Variation calendar model used in order to quantify and explain the effect of "lebaran". Then, transfer function model used to know the effect of inflation factor or price changing by using Consumer Price Indices (IHK) as "a Proxy variable" to the fluctuation of these number of passengers. The result of the analysis to three data as case studies show that the effect of crisis is only significant to the fluctuation of the number of plane passengers. Transfer function model yields three cases correlating with the number of train and plane passengers significantly influenced by IHK as a proxy of price fluctuation or inflation factor. Additionally, the result of this research gives the description that there is a big chance to use hybrid model of the available models, including intervention,variation calendar, transfer function and or GARCH models.